2018
DOI: 10.1097/j.pain.0000000000001205
|View full text |Cite
|
Sign up to set email alerts
|

Dilute lidocaine suppresses ectopic neuropathic discharge in dorsal root ganglia without blocking axonal propagation: a new approach to selective pain control

Abstract: Ectopic impulse discharge (ectopia) generated in the soma of afferent neurons in dorsal root ganglia (DRG) after nerve injury is believed to be a major contributor to neuropathic pain. The DRG is thus a prime interventional target. The process of electrogenesis (impulse generation) in the DRG is far more sensitive to systemically administered Na channel blockers than the process of impulse propagation along sensory axons. It should therefore be possible to selectively suppress DRG ectopia with local applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Low concentrations of local anesthetic applied to nerve targets have been shown to preferentially inhibit pain generation and transmission compared with motor and sensory function. 17,18 At the same time, given the need for relatively large injectate volumes to achieve spread, we employed the maximum recommended dose of bupivacaine/ropivacaine in the initial bolus to avoid excessively low local anesthetic concentrations. While the ability of dexamethasone and dexmedetomidine to augment analgesia in ESP blocks is currently unsubstantiated, we chose to add them to the local anesthetic mixture based on data from peripheral nerve blockade [19][20][21] and the principle that opioid sparing is best achieved by using as many multimodal analgesic strategies as possible 2 rather than relying on a single ''silver bullet''.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of local anesthetic applied to nerve targets have been shown to preferentially inhibit pain generation and transmission compared with motor and sensory function. 17,18 At the same time, given the need for relatively large injectate volumes to achieve spread, we employed the maximum recommended dose of bupivacaine/ropivacaine in the initial bolus to avoid excessively low local anesthetic concentrations. While the ability of dexamethasone and dexmedetomidine to augment analgesia in ESP blocks is currently unsubstantiated, we chose to add them to the local anesthetic mixture based on data from peripheral nerve blockade [19][20][21] and the principle that opioid sparing is best achieved by using as many multimodal analgesic strategies as possible 2 rather than relying on a single ''silver bullet''.…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell-patch clamp of rat dorsal horn neurons showed that lidocaine (100 μM) had an effect on the discharge characteristics of all 3 types of neurons, affecting the shape of the action potentials. VGSC partially blocked (the peak value of sodium current decreased by about approximately 50%); the same concentration of lidocaine could inhibited voltage-gated potassium channels in tetanic-firing neurons [ 12 , 13 ] ; thus, the different sensitivities of DRG ion channels could be exploited as a new method for blocking DRG differentiation. The resting potential of DRG neurons is determined by the balance of the delayed rectifier potassium channel and hyperpolarization-activated mixed inward current ( I h).…”
Section: Effect Of Lidocaine On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…Several reviews have outlined the importance that the PSN plays in the development and maintenance of chronic pain . Many of the pathophysiologic changes in neuronal function of PSNs observed in models of chronic pain are specifically located in the neuronal cell body, and these can include increased membrane excitability as well as the generation of ectopic action potentials . The PSNs also contain a t‐junction where the distal and primary axons combine with a stem axon that connects the soma.…”
Section: Introductionmentioning
confidence: 99%